2017
DOI: 10.1002/brb3.773
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin‐3 levels and delirium among postpartum intensive care unit women

Abstract: Objective: Inflammation correlates with delirium. Galectin-3 is a proinflammatory protein. This study aimed to determine relation of serum galectin-3 levels to delirium of postpartum intensive care unit (ICU) women. Materials and Methods:In this prospective observational study, serum galectin-3, S100B, and C-reactive protein levels of 412 postpartum ICU women and 412 healthy women were measured. Delirium and Acute Physiology and Chronic Health Care Evaluation II (APCHCE II) scores were recorded.Results: Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A comprehensive evaluation of the titles and abstracts resulted in the exclusion of 202 studies, leaving 39 articles as potentially relevant. 12 -50 Sixty-nine articles were identified using Google Scholar, none of which were included. No additional article was identified or selected from the reference lists of the retained studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive evaluation of the titles and abstracts resulted in the exclusion of 202 studies, leaving 39 articles as potentially relevant. 12 -50 Sixty-nine articles were identified using Google Scholar, none of which were included. No additional article was identified or selected from the reference lists of the retained studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The galectin-3 protein is involved in the phagocytic process of apoptotic hepatocytes [40]. Galectin-3 is one of the most frequently identified markers of liver disease [41] and is considered a prognostic biomarker in severe trauma or sepsis patients [42][43][44]. These findings indicated that hepatic inflammation and injury were attenuated when Arg was administered after CLP.…”
Section: Discussionmentioning
confidence: 97%
“…Dillon et al showed an association between levels of an inflammatory marker, C-reactive protein (CRP), and delirium (Dillon et al, 2017 ), and they also reported that the duration and severity of delirium can be predicted by high CRP levels (Vasunilashorn et al, 2017 ). Other groups reported associations of delirium with high levels of Galectin-3 and CRP among women in postpartum intensive care units (Zhu et al, 2017 ). A pro-inflammatory cytokine, IL-6, was elevated after surgery among patients with delirium compared to controls (Liu et al, 2013 ; Vasunilashorn et al, 2015 ).…”
Section: Introductionmentioning
confidence: 97%